1999
DOI: 10.3386/w7212
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Comparative Advantage: Chaotic or Coherent Patterns Across Time and Sector and U.S. Trading Partner?

Abstract: We map United States comparative advantage between 1980 and 1995, by trading partner and region, using Balassa's export-based index of Revealed Comparative Advantage (RCA). We find: temporally stable and ubiquitous US comparative advantage in differentiated producer goods (except disadvantage in Japan); somewhat less stable and less sweeping US disadvantage in standardized producer goods; chaotic and diverse patterns of US RCA in consumer goods (especially in the Chinese market). Our most significant findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
0
34
0
2
Order By: Relevance
“…According to J.P.Joshi, "as many as 42 items of trade between India and the Gulf have been identified which include silver, copper, tortoise shell, ivory, cloth, carnelian, pearls, tin and precious stones". Richardson & Zhang (1999) have used the Balassa index of RCA for the U.S to analyse the patterns of variation across time, sectors and regions. They find the patterns to differ across different parts of the world, over time as also for different levels of aggregation of the export data.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…According to J.P.Joshi, "as many as 42 items of trade between India and the Gulf have been identified which include silver, copper, tortoise shell, ivory, cloth, carnelian, pearls, tin and precious stones". Richardson & Zhang (1999) have used the Balassa index of RCA for the U.S to analyse the patterns of variation across time, sectors and regions. They find the patterns to differ across different parts of the world, over time as also for different levels of aggregation of the export data.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Ferto and Hubbard (2002) used these modifications of the RCA index in the context of agricultural trade between Hungary and EU. Other important studies based on RCA approach include Yeats (1997), Richardson and Zhang (1999), Yue (2001), Bender and Li (2002), Weiss (2004), Lall and Albaladejo (2003) and Lall and Weiss (2004).…”
Section: Theoretical Developments and Empirical Studiesmentioning
confidence: 99%
“…It can be concluded that recent further increases in Mercosur's tariffs against nonmembers are likely to exacerbate the magnitude of trade diversion. Richardson and Zhang (1999) compared US export performance between 1980 and 1995 using Balassa's export-based index of Revealed Comparative Advantage with 38 of its large trading partners, aggregating them into six regional groups, except China and Japan that are treated separately. They found temporally stable and ubiquitous US comparative advantage in differentiated producer goods (except disadvantage in Japan); somewhat less stable and less sweeping US disadvantage in standardised producer goods; and chaotic and diverse patterns of US RCA in consumer goods (especially in the Chinese market).…”
Section: Review Of Literaturementioning
confidence: 99%